2009
DOI: 10.1016/j.neuroscience.2009.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Sources of cholinergic input to the inferior colliculus

Abstract: We combined retrograde tracing with immunohistochemistry for choline acetyltransferase to identify the source of cholinergic input to the inferior colliculus (IC). Injection of a retrograde tracer into one IC labeled cells in many brainstem nuclei. Retrogradely-labeled cells that were also immunoreactive for choline acetyltransferase were identified in two nuclei in the midbrain tegmentum: the pedunculopontine tegmental nucleus (PPT) and the laterodorsal tegmental nucleus (LDT). More PPT and LDT cells project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 72 publications
(109 reference statements)
5
60
0
Order By: Relevance
“…BDA was chosen as it has proven to be a superior anterograde tracer in our hands and others (Ling et al, 2012). For subcortical injections, BDA was injected iontophoretically using 5 A positive current pulses (50% duty cycle) for 10 -20 min.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…BDA was chosen as it has proven to be a superior anterograde tracer in our hands and others (Ling et al, 2012). For subcortical injections, BDA was injected iontophoretically using 5 A positive current pulses (50% duty cycle) for 10 -20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies that have plotted the terminals in the LC arising from the spinal trigeminal nucleus have shown that they terminate in distinctive clusters that resemble the input patterns from the dorsal column nuclei and somatosensory cortex (Wise and Jones, 1977;Wiberg and Blomqvist, 1984;Wiberg et al, 1987). Input to the LC from auditory brainstem structures, such as the cochlear nucleus and the lateral lemniscus, is largely restricted to layer 3, suggesting that this input is extramodular (Coleman and Clerici, 1987;González-Hernández et al, 1996;Gabriele et al, 2000;Malmierca et al, 2005;Loftus et al, 2008). In a dual anterograde tract-tracing study, Zhou and Shore (2006) labeled afferents to the LC from the cochlear nucleus and spinal trigeminal nucleus in the guinea pig.…”
Section: Connectional Modularity Of the Lcmentioning
confidence: 99%
See 3 more Smart Citations